Mrs. Harris goes to Paris [videorecording (DVD)] - Manville, Lesley; Huppert, Isabelle; Wilson, Lambert; Baptista, Alba, 1997-; Bravo, Lucas, 1988-; Thomas, Ellen (Actress); Williams, Rose, 1994-; Isaacs, Jason, 1963-; Gallico, Paul, 1897-1976 (Universal, 2022)
In 1950s London, a widowed cleaning lady falls madly in love with a couture Dior dress, deciding she must have one of her own. After working to raise the funds to pursue her dream, she embarks on an adventure to Paris that will change not only her own outlook, but the very future of the House of Dior.